Penguatan Islandpreneurship dalam Pengelolaan Pariwisata Berkelanjutan: Pelatihan Manajemen Sampah, Bahasa Inggris, dan Layanan Wisata bagi Pokdarwis Bukit Idat di Desa Dalil: Strengthening Islandpreneurship in Sustainable Tourism Management: Training on Waste Management, English Language, and Tourism Services for Pokdarwis Bukit Idat in Dalil Village - Aryansyah, Ary Fakturrachman; Amalia, Resti; Basri, Mursyid Hasan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This community engagement program aims to enhance the capacity of Pokdarwis Bukit Idat in managing community-based tourism in Dalil Village, Bangka Regency. The Islandpreneurship approach was applied through training in waste management, tourism service improvement using digital marketing, and English language skills to strengthen competitiveness. Methods included module development, field practice, service simulations, and participatory evaluation. The results showed improved skills in waste sorting, confidence in serving foreign tourists in English, and the use of social media for destination promotion. Furthermore, local-based educational tourism product ideas emerged. This program demonstrates that Islandpreneurship can foster a sustainable, innovative tourism ecosystem based on local community empowerment.